Instrumentation for high-dose, high-resolution dosimetry for microbeam radiation therapy using samarium-doped fluoroaluminate and fluorophosphate glass plates. (16th October 2019) - Chicilo, F; Okada, G; Belev, G; Chapman, D; Edgar, A; Curry, R J; Kasap, S
Abstract: We show that 1% Sm-doped fluoroaluminate (FA) glass plate and a suitably modified fluorescence confocal microscope provide an excellent radiation detection platform for high-dose measurements at high resolution down to the micron scale. We have used a custom-modified fluoroscopic confocal microscope apparatus to scan, separate, detect, and digitize the photoluminescence (PL) signals from Sm 3+ and Sm 2+ ions in both FA and fluorophosphate (FP) glasses within a selected focal depth of the microscope below the sample surface. The response ( R ) of Sm-doped FA and FP glass plates to incident x-ray radiation was studied in detail in which R was defined as the difference in the ratio of PL signals from Sm 2+ and Sm 3+ before and after irradiation. We report on a number of important issues related to the use of these Sm-doped FA and FP glass plates in microbeam radiation therapy (MRT) dosimetry: The dependence of the Sm 3+ to Sm 2+ conversion, and hence R on the dose rate over some four orders of magnitude; the energy dependence of R at a given dose rate for both FA and FP samples with various concentrations of Sm 3+ doping; R versus dose behavior at different energies up to 2000 Gyair and the derivation of the detector calibration curves; the stability of the Sm-doped plates after they have been exposed; the instrumental limits of the present measurement technique.